The Meaning of Joshou Song Lyric in Touken Ranbu Musical Theater - Santiar, Lea; Rachmaniar, Siti (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2022)
The term joshou (prologue) is usually placed at the beginning of a story. However, musical theatre Touken Ranbu Musubi no Hibiki Hajimari no Ne does the exact opposite. This raises the question whether there is a particular purpose for using the term joshou, and not using the term kessho (epilogue). To answer this question, the author uses Riffaterre's theory of poetry semiotics in interpreting the song Joshou. This research uses a qualitative descriptive method by analyzing the data collected and explaining the results of the analyzed data. The data used are the lyrics of Joshou's song from Touken Ranbu’s musical theater. The research steps taken are heuristic reading, connecting Joshou's song lyrics with the musical theater story, performing hermeneutic reading, looking for discontinuity of expression, determining matrix, model, and variant. After analysis, the results show that the song titled Joshou (prologue) is sung at the end of the musical theater performance because there is a message contained in the song in the form of the end of a story is the beginning of the following story. The term kessho (epilogue) is not used since it does not show that the story has ended.